2020
DOI: 10.2174/1381612826666200114105515
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based Biomarkers of Alzheimer’s Disease: The Long and Winding Road

Abstract: Background: Blood-based biomarkers can be very useful in formulating new diagnostic and treatment proposals in the field of dementia, especially in Alzheimer’s disease (AD). However, due to the influence of several factors on the reproducibility and reliability of these markers, their clinical use is still very uncertain. Thus, up-to-date knowledge about the main blood biomarkers that are currently being studied is extremely important in order to discover clinically useful and applicable tools, which could als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 196 publications
0
15
0
2
Order By: Relevance
“…Biomarkers for AD are highly needed in clinic, especially those based on samples of easy collection, such as blood [5,10]. Currently, validated AD biomarkers are represented by neuroimage measures and quanti cation of the βA peptide, t-tau and p-tau derived from CSF, both requiring speci c equipment or invasive procedures, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarkers for AD are highly needed in clinic, especially those based on samples of easy collection, such as blood [5,10]. Currently, validated AD biomarkers are represented by neuroimage measures and quanti cation of the βA peptide, t-tau and p-tau derived from CSF, both requiring speci c equipment or invasive procedures, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Even in non-disease situations, the exchange of molecules and proteins between CSF and blood is well reported, despite the limitation imposed by BBB [9]. In this regard, several blood-based AD biomarker candidates have been described, including the α-secretase ADAM10 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several blood-based AD biomarker candidates have been described, including the ADAM10 [10], which is the main α-secretase participating in the nonamyloidogenic cleavage of APP in neurons, thus having a protective function against this dementia [11]. ADAM10 can be found in different isoforms, and we have already reported that the membrane-bound platelet ADAM10 is active cleaving a fluorogenic substrate, while the isoform found soluble in plasma and CSF is inactive [12].…”
Section: Introductionmentioning
confidence: 95%
“…While CSF is considered an ideal source when it directly interacts with the extracellular space of the brain, CSF sampling is not trivial. There are trials of using peripheral blood to measure oxidative stress changes in neurodegenerative diseases 97‐99 . Therefore, direct comparison of such measurement between CSF and serum should be performed in future.…”
Section: Csf Oxidative Stress Markers In Ad In Vivomentioning
confidence: 99%